Design of Rectangular Microstrip Patch Antenna Incorporated with Innovative Metamaterial Structure for Dual band operation and Amelioration in Patch Antenna Parameters with Negative µ and ? - Garg, Bimal; Verma, Rahul Dev; Samadhiya, Ankit (International Journal of Engineering and Technology, 2012)
In this work a dual band rectangular microstrip patch antenna along with the innovative metamaterial structure is proposed at a height of 3.2mm from the ground plane, which consists of a rectangular geometry incorporated with c shaped structure. This work is mainly focused on increasing the potential parameters of microstrip patch antennas and analyzing the dual band operation of proposed antenna. The proposed antenna is designed to resonate at 2.478GHz and 2.919GHz frequency. The impedance bandwidth of the patch antenna along with the proposed metamaterial structure at 2.478GHz is improved by 20.4MHz and return loss is reduced by 20.128dB. At 2.919GHz the impedance bandwidth is improved by 25.4MHz and return loss is reduced by 19.564dB. For verifying that the proposed metamaterial structure possesses Negative values of Permeability and Permittivity within the operating frequency ranges, Nicolson-Ross-Weir method (NRW) has been employed. For simulation purpose CST-MWS Software has been used.